Factors associated with knowledge about pharmacological management of pregnant women in Peruvian dental students: a logistic regression analysis - Flores-Montalvo, Elizabeth (2023)
Background: Clinical management to maintain or restore oral health through the use of drugs during pregnancy is crucial, since at this stage physiological changes significantly influence the absorption, distribution and elimination of the drug, considering also that excessive administration of drugs during this period may have adverse effects on the mother and/or fetus. Therefore, the aim of the present study was to evaluate the factors associated with knowledge of pharmacological management of pregnant women in dental students of a Peruvian university located in the capital and province. Methods: This analytical, cross-sectional, prospective and observational study assessed 312 Peruvian dental students from third to fifth year of study between February and April 2022. A validated questionnaire of 10 closed questions was used to measure knowledge about pharmacological management in pregnant women. A logit model was used to assess the influence of the variables: gender, age, year of study, marital status, place of origin and area of residence. A significance of p < 0.05 was considered. Results: The 25.96, 55.13 and 18.91% of the dental students showed poor, fair and good knowledge about pharmacological management in pregnant women; respectively. In addition, it was observed that students under 24 years of age and those from the capital were significantly (p < 0.05) 44% less likely to have poor knowledge of pharmacological management in pregnant women compared to those aged 24 years or older (OR = 0.56; CI: 0.34–0.92) and those from the province (OR = 0.56; CI: 0.32–0.98); respectively. Finally, those in their third and fourth year of study were significantly three times more likely to have poor knowledge (OR = 3.17; CI: 1.68–5.97 and OR = 3.88; CI: 2.07–7.31; respectively) compared to fifth year dental students. Conclusion: The knowledge of dental students about pharmacological management in pregnant women was predominantly of fair level. In addition, it was observed that being under 24 years of age and being from the capital city were protective factors against poor knowledge, while being a third- and fourth-year student was a risk factor. Finally, gender, marital status and area of residence were not influential factors in the level of knowledge.